Curing the First Amendment Scrutiny Muddle Through a Breyer-Based Blend Up? Toward a Less Categorical, More Values-Oriented Approach for Selecting Standards of Judicial Review - Clay Calvert (Washington University Journal of Law & Policy, 2021)
This Article argues that the United States Supreme Court should significantly alter its current categorical approach for discerning standards of judicial review in free-speech cases. The present system should become nondeterminative and be augmented with a modified version of Justice Stephen Breyer’s long-preferred proportionality framework. Specifically, the Article’s proposed tack fuses facets of today’s policy, which largely pivots on distinguishing content-based laws from content-neutral laws and letting that categorization determine scrutiny, with a more nuanced, values-and-interests methodology. A values-and-interests formula would allow the Court to climb up or down the traditional ladder of scrutiny rungs – strict, intermediate or rational basis – depending on whether a statute jeopardizes a core rationale for safeguarding free expression and the degree to which that rationale is threatened. Given the frequent divide along partisan lines on today’s Supreme Court over scrutiny in First Amendment speech cases, a two-tiered approach that blends aspects of a categorical strategy with a values-and-interests tack provides a path forward as the Court moves fully into the third decade of the twenty-first century.
Keywords: judicial review; review; scrutiny; free speech; First Amendment; proportionality; values; interest; Breyer; Supreme Court; Supreme Court of the United States; SCOTUS